Activation of cryptic donor splice sites by non-coding and coding PAX6 variants contributes to congenital aniridia. Issue 5 (29th March 2021) - Tarilonte, Maria; Ramos, Patricia; Moya, Jennifer; Fernandez-Sanz, Guilermo; Blanco-Kelly, Fiona; Swafiri, Saoud Tahsin; Villaverde, Cristina; Romero, Raquel; Tamayo, Alejandra; Gener, Blanca; Calvas, Patrick; Ayuso, Carmen; et al.
Abstract : Background: The paired-domain transcription factor paired box gene 6 (PAX6) causes a wide spectrum of ocular developmental anomalies, including congenital aniridia, Peters anomaly and microphthalmia. Here, we aimed to functionally assess the involvement of seven potentially non-canonical splicing variants on missplicing of exon 6, which represents the main hotspot region for loss-of-function PAX6 variants. Methods: By locus-specific analysis of PAX6 using Sanger and/or targeted next-generation sequencing, we screened a Spanish cohort of 106 patients with PAX6 -related diseases. Functional splicing assays were performed by in vitro minigene approaches or directly in RNA from patient-derived lymphocytes cell line, when available. Results: Five out seven variants, including three synonymous changes, one small exonic deletion and one non-canonical splice variant, showed anomalous splicing patterns yielding partial exon skipping and/or elongation. Conclusion: We describe new spliceogenic mechanisms for PAX6 variants mediated by creating or strengthening five different cryptic donor sites at exon 6. Our work revealed that the activation of cryptic PAX6 splicing sites seems to be a recurrent and underestimated cause of aniridia. Our findings pointed out the importance of functional assessment of apparently silent PAX6 variants to uncover hidden genetic alterations and to improve variant interpretation for genetic counselling in aniridia.